The impact of climate change on countries’ interdependence on genetic resources for food and agriculture: An executive summary - Fujisaka, S.; Williams, D.; Halewood, Michael (2010)
The System-wide Genetic Resources Programme (SGRP) of the CGIAR coordinated the development of a background study paper entitled ‘The Impact of Climate Change on Countries Interdependence on Genetic Resources for Food and Agriculture’ for the Twelfth Session of the FAO Commission on Genetic Resources for Food and Agriculture. The purpose of the paper was to contribute to the Commission’s consideration of policies and arrangements for access and benefit-sharing for genetic resources for food and agriculture. This document is an executive summary of that paper.